Low-temperature high-voltage high-rate lithium battery electrolyte and application thereof
Patent Information
- Application Number
- CN202611152943.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-16
AI Technical Summary
然而,仅靠溶剂化结构调控有时仍不足以获得长期循环稳定的界面,因此需要引入功能性成膜添加剂,与氟磺酰类溶剂协同作用,进一步优化界面膜的组分、厚度与均匀性
[0028] (1) The electrolyte of the present invention significantly alters the solvation structure of lithium ions by introducing fluorosulfonyl solvents. Combined with nitrile solvents and specific film-forming additives, and by controlling their dosage, the electrolyte can maintain a high voltage window while possessing ultra-low freezing point, high ionic conductivity, high voltage stability, and good compatibility with the negative electrode.
Smart Images

Figure CN122931049A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery technology, and relates to an electrolyte for a low-temperature, high-voltage, high-rate lithium battery and its application. Background Technology
[0002] To drive the new energy industry towards higher energy density, battery technology is facing an urgent need for upgrades to key materials. As the core medium for ion transport in batteries, the performance of the electrolyte directly determines the feasibility of high-voltage battery systems. While commercially available carbonate-based electrolytes are widely used due to their mature processes and low cost, their inherent defects in high-voltage scenarios are becoming increasingly apparent. When the battery operating voltage exceeds 4.5V, carbonate molecules are prone to oxidative decomposition on the positive electrode surface, triggering gas release and interfacial side reactions, leading to rapid capacity decay and safety hazards. This significantly contradicts the development needs of next-generation high-voltage positive electrode materials such as lithium-rich manganese-based and high-nickel ternary materials.
[0003] At low temperatures, carbonate electrolytes exhibit increased viscosity and decreased ionic conductivity, while Li... + The decreased diffusion rate in the positive and negative electrodes and electrolyte leads to severe polarization and a decline in battery performance. Commercial electrolytes typically contain 30%–50% ethylene carbonate (EC), but EC has a high freezing point of 36.4°C. This causes the electrolyte viscosity to increase and the ion transport number to decrease at low temperatures, and in severe cases, even solidification occurs, thus limiting the performance of lithium metal batteries at low temperatures. For example, Chinese patent application CN117133977A discloses a carbonate-based electrolyte comprising carbonates, ethers, lithium salts, lithium nitrate, and planar macrocyclic compounds. By introducing lithium nitrate and planar macrocyclic compounds, high-voltage positive electrode materials can be used; however, its maximum voltage is only 4.2V, and its specific capacity shows significant decay at a 3C rate.
[0004] Nitrile solvents possess excellent properties such as low melting points (e.g., acetonitrile has a melting point of -45℃, and butadiene nitrile has a melting point of -112℃), high dielectric constant, and low viscosity, making them ideal additives for reducing the viscosity of electrolytes at low temperatures. Most nitrile solvents also exhibit excellent oxidative stability, and the cyano groups in their molecules can complex with transition metals in the cathode material, effectively inhibiting transition metal dissolution and preventing damage to the cathode structure. However, nitrile solvents have insufficient reducing stability and are prone to side reactions with the lithium metal anode, leading to continuous degradation of the anode interface, a decrease in coulombic efficiency, and a surge in interfacial impedance.
[0005] Fluorosulfonyl solvents possess extremely low melting points (some below -80°C), high dielectric constants, and good antioxidant stability, and their weak coordination ability can modulate the lithium-ion solvation structure. However, solvation structure modulation alone is sometimes insufficient to obtain a long-term cycling-stable interface. Therefore, it is necessary to introduce functional film-forming additives to synergistically work with fluorosulfonyl solvents to further optimize the composition, thickness, and uniformity of the interfacial film. Summary of the Invention
[0006] In view of the above-mentioned problems existing in the electrolyte of the prior art, the first objective of the present invention is to provide a low-temperature, high-voltage, and high-rate lithium battery electrolyte, which, through the synergistic effect of nitrile solvents, fluorosulfonyl solvents and film-forming additives, simultaneously possesses ultra-low freezing point, high ionic conductivity, high voltage stability and good compatibility with the negative electrode.
[0007] The second objective of this invention is to provide an application of a low-temperature, high-voltage, and high-rate lithium battery electrolyte. By applying it to lithium batteries, the synergistic effect of the components in the electrolyte is utilized to achieve comprehensive protection of the positive and negative electrode interfaces, enabling the lithium battery to have excellent rate performance and cycle stability under low-temperature and high-voltage conditions.
[0008] To achieve the above-mentioned technical objectives, the present invention provides a low-temperature, high-voltage, and high-rate lithium battery electrolyte, comprising a solvent, a film-forming additive, and a first lithium salt; the solvent is composed of a nitrile solvent and a fluorosulfonyl solvent in a volume percentage of (40~70):(60~30); the film-forming additive comprises an ester solvent and a second lithium salt in a mass ratio of (5~10):1; the amount of the film-forming additive is 2~10 wt% of the total mass of the electrolyte; the ester solvent comprises at least one of carbonate solvents, sulfate solvents, and sulfite solvents, and the second lithium salt comprises at least one of lithium difluorophosphate, lithium dioxalateborate, and lithium difluoroborate.
[0009] The electrolyte of this invention can maintain a high voltage window while possessing an ultra-low freezing point, high ionic conductivity, high voltage stability, and good compatibility with the negative electrode. The key lies in the synergistic effect of nitrile solvents, fluorosulfonyl solvents, and specific film-forming additives, as well as the control of their dosage. Specifically, nitrile solvents are commonly used in low-temperature batteries, supporting high-voltage operation up to 4.9 V. However, in existing nitrile solvent systems, due to the low molecular orbital energy levels occupied by nitrile solvents, they are prone to reduction and decomposition on the negative electrode surface, forming a series of soluble dimers, trimers, and oligomers. This leads to continuous degradation of the negative electrode interface, coulombic efficiency decay, and a surge in interfacial impedance, thereby limiting the stability of the battery material and the maintenance of high voltage. Simultaneously, it is also impossible to maintain good rate performance of the battery. In this invention, the introduction of fluorosulfonyl solvents with weak coordination ability and ultra-low melting points significantly alters the solvation structure of lithium ions, reducing the participation of nitrile solvents in the lithium-ion solvation sheath. This causes lithium ions to preferentially exist as contact ion pairs (CIPs) and aggregated ion pairs (AGGs), rather than as solvent-separated ion pairs (SSIPs). Anions (such as TFSIs)... - The lithium ions preferentially enter the first solvation sheath layer (SEI) and undergo preferential reduction on the negative electrode surface, generating an SEI layer rich in inorganic substances (such as LiF). This SEI layer effectively blocks direct contact between nitrile solvents and the negative electrode, thus solving the problem of unstable reduction of nitrile solvents and ensuring the continuous high-voltage oxidation stability of the battery. In addition, by controlling the mass ratio of fluorosulfonyl solvents to nitrile solvents, the CIP / AGG solvation structure induced by fluorosulfonyl solvents significantly reduces the desolvation energy barrier of lithium ions on the negative electrode surface. Combined with the solvent advantage of nitrile solvents themselves, the complexation of cyano groups with the transition metal of the positive electrode suppresses the dissolution of the transition metal under high voltage, thereby significantly improving the low-temperature performance, high-rate performance, and long-term stability at high voltage of the battery.
[0010] On the other hand, this invention employs a film-forming additive composed of an ester solvent and a second lithium salt to simultaneously enhance interfacial film formation. The ester solvent can be reduced and polymerized on the negative electrode surface to form a flexible organic polymer component, thereby endowing the SEI layer with good flexibility and adapting to the volume changes of the negative electrode during charging and discharging. Meanwhile, the anions of the second lithium salt are reduced and decomposed on the negative electrode surface to generate inorganic components rich in LiF, Li2O, and containing B or P inorganic substances, giving the SEI layer high mechanical strength and excellent lithium-ion conductivity. The two can also form an organic-inorganic composite structure at the interface, which not only ensures the compactness of the SEI layer to prevent continuous electrolyte penetration and decomposition, but also avoids the surge in interfacial impedance caused by the embrittlement of traditional SEI at low temperatures, ensuring rapid transport of lithium ions at high rates. More importantly, the CEI film formed on the positive electrode surface by the film-forming additive effectively blocks the direct contact between the bulk electrolyte and the high-voltage positive electrode, further inhibiting the oxidative decomposition of the solvent under high voltage and improving the long-term stability of the electrolyte under high voltage windows. Experiments have shown that when nitrile solvents and fluorosulfonyl solvents are outside the volume percentage range controlled by this invention, or when ester solvents and the second lithium salt in the film-forming additives are outside the mass ratio range of this invention, the overall performance of the electrolyte will decrease. As a result, the battery cannot maintain a high voltage window while also possessing an ultra-low freezing point, high ionic conductivity, high voltage stability, and good compatibility with the negative electrode.
[0011] As a preferred embodiment, the nitrile solvent is at least one of C2-C5 alkyl nitrile and fluorinated C2-C5 alkyl nitrile.
[0012] As a preferred embodiment, the fluorosulfonyl solvent is at least one selected from methyl fluorosulfonyl difluoroacetate, N-pyrrolidinyl sulfonyl fluoride, N,N-dimethylsulfonyl fluoride, N,N-diethylsulfonyl fluoride, ethylsulfonyl fluoride, dimethylsulfonyl fluoride, and 1-butanesulfonyl fluoride.
[0013] As a preferred embodiment, the carbonate solvent includes at least one of ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, and vinylene sulfate; the sulfate solvent includes at least one of vinylene sulfate and propylene sulfate; and the sulfite solvent includes vinylene sulfite.
[0014] As a preferred embodiment, the solvent is composed of isobutyronitrile and methyl fluorosulfonyl difluoroacetate.
[0015] As a preferred embodiment, the film-forming additive includes fluoroethylene carbonate and lithium difluorophosphate.
[0016] Experiments revealed that when a further optimized solvent combination was used, the ester group of methyl fluorosulfonyl difluoroacetate ensured good miscibility between the solvent and nitrile solvents, fluoroethylene carbonate, and other components. The strong electron-withdrawing effect and weak coordination characteristics of its fluorosulfonyl group and difluoromethylene group, combined with the steric hindrance effect of the isobutyronitrile branched structure, jointly weakened the excessive coordination of lithium ions by nitrile solvents, promoting anion enrichment in the lithium-ion solvation sheath. This significantly reduced the desolvation energy barrier of lithium ions on the negative electrode surface, suppressing negative electrode degradation caused by insufficient reduction stability of nitrile solvents. Furthermore, fluoroethylene carbonate and lithium difluorophosphate could jointly form an organic-inorganic composite SEI layer with higher mechanical strength, better flexibility, and high lithium-ion conductivity, more effectively suppressing side reactions under high voltage and further improving the low-temperature performance of the battery.
[0017] As a preferred embodiment, the volume percentage of nitrile solvent and fluorosulfonyl solvent in the solvent is (45~50):(55~50). More preferably, the volume percentage of nitrile solvent and fluorosulfonyl solvent in the solvent is 50:50. Experiments have shown that the best results are achieved when both are added in equal proportions.
[0018] As a preferred embodiment, the amount of the film-forming additive is 8-10 wt% of the total electrolyte mass. Experiments have shown that when the amount of the film-forming additive is too low, the organic-inorganic composite SEI layer formed on the negative electrode surface by the ester solvent and the second lithium salt, as well as the CEI film on the positive electrode surface, are not dense enough. This fails to effectively block the direct contact between the nitrile solvent and the negative electrode, and also makes it difficult to suppress the dissolution of the positive electrode transition metal and the oxidative decomposition of the solvent under high voltage. Consequently, interfacial side reactions persist, coulombic efficiency decreases, and high-voltage stability is insufficient. Conversely, excessive addition results in an overly thick interfacial film, which in turn reduces ionic conductivity, rate performance, and low-temperature performance.
[0019] As a preferred embodiment, the mass ratio of the ester solvent and the second lithium salt in the film-forming additive is in the range of (8~10):1. When a further preferred mass ratio range is adopted, a better organic-inorganic composite structure can be formed, and the stability of the electrolyte under high voltage can be further improved.
[0020] As a preferred embodiment, the first lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiDFOB), lithium bisfluorosulfonylimide (LiFSI), lithium trifluoromethanesulfonate (LiTFSI), and lithium bistrifluoromethanesulfonylimide (Li(C2F5SO2)2N).
[0021] As a preferred embodiment, the concentration of the first lithium salt in the electrolyte is 0.3~2 mol / L. More preferably, it is 0.5~2 mol / L.
[0022] As a preferred embodiment, the electrolyte has an applicable voltage range of 2.8~4.5V, a temperature range of -40~25℃, and a rate range of 0.1~5℃. Through the electrolyte combination of the present invention, the advantage of nitrile solvents being adaptable to high voltages can be maintained, while also achieving excellent low-temperature performance and rate performance of the electrolyte, especially long-cycle performance at low temperatures.
[0023] Finally, this invention also provides an application of a low-temperature, high-voltage, and high-rate lithium battery electrolyte, which is then used in lithium batteries. By utilizing the synergistic effect of the components in the electrolyte, comprehensive protection of the positive and negative electrode interfaces is achieved, enabling the battery to exhibit excellent rate performance and cycle stability under low-temperature and high-voltage conditions.
[0024] As a preferred embodiment, the active material of the positive electrode active material layer on the positive electrode sheet of the lithium battery is selected from at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate, and lithium manganese oxide.
[0025] As a preferred embodiment, the lithium battery is a pouch lithium battery, an aluminum-cased lithium battery, or a cylindrical lithium battery.
[0026] As a preferred embodiment, the lithium battery has a discharge capacity of not less than 110mAh / g at 2.8~4.5V, -40℃, and 5C current.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] (1) The electrolyte of the present invention significantly alters the solvation structure of lithium ions by introducing fluorosulfonyl solvents. Combined with nitrile solvents and specific film-forming additives, and by controlling their dosage, the electrolyte can maintain a high voltage window while possessing ultra-low freezing point, high ionic conductivity, high voltage stability, and good compatibility with the negative electrode.
[0029] (2) The film-forming additive of the present invention is composed of ester solvent and second lithium salt. The addition of the two enhances the interfacial film formation, endows the SEI layer with good flexibility, high mechanical strength and excellent lithium ion conduction ability, and the two can form an organic-inorganic composite structure at the interface, further inhibiting the oxidative decomposition of the solvent under high pressure and improving the long-term stability of the electrolyte under high voltage window.
[0030] (3) The secondary battery assembled with the electrolyte of the present invention can have good charge and discharge performance, good cycle stability and excellent low temperature performance in the voltage range of 2.8~4.5V. It can form a stable and low impedance SEI film, thereby improving the initial capacity and cycle life of the lithium battery.
[0031] (4) The present invention applies the electrolyte to lithium batteries, and the resulting lithium batteries retain up to 97.61% capacity after 160 cycles at -40℃ and 0.2C current. Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 Low-temperature (-40°C) cycle performance of nickel-cobalt-manganese ternary lithium metal coin cells prepared with the electrolytes obtained in Examples 3, 4, 1, 6 and 9.
[0034] Figure 2 The low-temperature (-40°C) rate performance of nickel-cobalt-manganese ternary lithium metal button batteries prepared with the electrolyte obtained in Example 4 and the electrolyte obtained in Comparative Example 1.
[0035] Figure 3 The graph shows the cycling performance of the nickel-cobalt-manganese ternary lithium metal coin cell prepared with the electrolyte obtained in Example 4 after 160 cycles at -40°C. Detailed Implementation
[0036] The technical solution of the present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0037] In the following examples and comparative examples, the electrolyte was prepared by mixing the solvent in proportion and then adding lithium salt and film-forming additives in a glove box under an argon atmosphere (moisture content <0.01ppm, oxygen content <0.01ppm).
[0038] The obtained electrolyte is assembled into a coin cell, with the positive electrode being a nickel-cobalt-manganese ternary cathode, the negative electrode being lithium metal, and the separator being a polyolefin membrane.
[0039] Example 1
[0040] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0041] The fluorosulfonyl solvent used was N,N-dimethylsulfonyl fluoride, and the nitrile solvent used was butyronitrile. The volume percentage of N,N-dimethylsulfonyl fluoride and butyronitrile was 50%:50%.
[0042] The film-forming additive is composed of fluoroethylene carbonate and lithium dioxalate borate in a mass ratio of 1:1; the amount of film-forming additive added is 5 wt% of the total mass of the electrolyte.
[0043] The first lithium salt is composed of lithium hexafluorophosphate and lithium tetrafluoroborate in a molar ratio of 9:1, and the concentration of the first lithium salt in the electrolyte is 1 mol / L.
[0044] Example 2
[0045] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0046] The fluorosulfonyl solvent used was N,N-dimethylsulfonyl fluoride, and the nitrile solvent used was fluoroacetonitrile. The volume percentage of N,N-dimethylsulfonyl fluoride and fluoroacetonitrile was 60%:40%.
[0047] The film-forming additive is composed of fluoroethylene carbonate and lithium dioxalate borate in a mass ratio of 1:1; the amount of film-forming additive added is 3 wt% of the total mass of the electrolyte.
[0048] The first lithium salt is lithium bis(fluorosulfonyl)imide, and the concentration of the first lithium salt in the electrolyte is 1 mol / L.
[0049] Example 3
[0050] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0051] The fluorosulfonyl solvents used were ethyl fluorosulfonyl and N,N-dimethylsulfonyl fluoride, and the nitrile solvents used were fluoroacetonitrile and isobutyronitrile. The volume percentages of ethyl fluorosulfonyl, N,N-dimethylsulfonyl fluoride, fluoroacetonitrile, and isobutyronitrile were 25%:25%:25%:25%.
[0052] The film-forming additive is composed of fluoroethylene carbonate and lithium dioxalate borate in a mass ratio of 1:1; the amount of film-forming additive added is 5 wt% of the total mass of the electrolyte.
[0053] The first lithium salt is lithium bis(fluorosulfonyl)imide, and the concentration of the first lithium salt is 1 mol / L.
[0054] Example 4
[0055] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0056] The fluorosulfonyl solvent used was methyl fluorosulfonyl difluoroacetate, and the nitrile solvent used was isobutyronitrile. The volume percentage of methyl fluorosulfonyl difluoroacetate and isobutyronitrile was 50%:50%.
[0057] The film-forming additive is composed of fluoroethylene carbonate and lithium difluorophosphate in a mass ratio of 10:1; the amount of film-forming additive added is 10 wt% of the total mass of the electrolyte.
[0058] The first lithium salt is composed of lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate in a molar ratio of 8:2, and the concentration of the first lithium salt is 1 mol / L.
[0059] In this embodiment, the obtained electrolyte is also assembled into a nickel-cobalt-manganese ternary lithium metal button battery, and its low-temperature performance is tested.
[0060] Depend on Figure 2 It can be seen that the discharge capacity is still 117.48 mAh / g at -40℃ and 5C current. In contrast, conventional carbonate electrolytes have almost no capacity at -40℃.
[0061] And by Figure 3 It is known that it has excellent low-temperature cycling performance, with a capacity retention rate of up to 97.61% after 160 cycles at -40℃ and 0.2C current.
[0062] Comparative Example 1
[0063] The difference between the electrolyte in this comparative example and the example is that the organic solvent is prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of 24:24:36.
[0064] Its performance under low-temperature conditions was tested.
[0065] Comparative Example 2
[0066] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0067] The fluorosulfonyl solvents used were methyl fluorosulfonyl difluoroacetate and N,N-diethylsulfonyl fluoride, and the nitrile solvent used was isovaleronitrile. The volume percentages of methyl fluorosulfonyl difluoroacetate, N,N-diethylsulfonyl fluoride, and isovaleronitrile were 30%:30%:40%.
[0068] The film-forming additive is composed of propylene sulfate and vinyl sulfite in a mass ratio of 1:1; the amount of film-forming additive added is 2 wt% of the total mass of the electrolyte.
[0069] The first lithium salt is composed of lithium hexafluorophosphate and lithium difluorosulfonylimide in a molar ratio of 1:1, and the concentration of the first lithium salt in the electrolyte is 0.8 mol / L.
[0070] Comparative Example 3
[0071] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0072] The fluorosulfonyl solvent used was 1-butanesulfonyl fluoride, and the nitrile solvent used was isobutyronitrile. The volume percentage of 1-butanesulfonyl fluoride and isobutyronitrile was 30%:70%.
[0073] The film-forming additive is composed of fluoroethylene carbonate and vinylene carbonate in a mass ratio of 1:1, and the amount of film-forming additive added is 2 wt% of the total mass of the electrolyte.
[0074] The first lithium salt is composed of lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate in a molar ratio of 8:2, and the concentration of the first lithium salt in the electrolyte is 1 mol / L.
[0075] Comparative Example 4
[0076] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0077] The fluorosulfonyl solvents used were methyl fluorosulfonyl difluoroacetate and N,N-dimethylsulfonyl fluoride, and the nitrile solvents used were acetonitrile and butyronitrile. The volume percentages of methyl fluorosulfonyl difluoroacetate, N,N-dimethylsulfonyl fluoride, acetonitrile, and butyronitrile were 30%:30%:20%:20%.
[0078] The film-forming additive is composed of propylene sulfate and vinyl sulfite in a mass ratio of 1:1; the amount of film-forming additive added is 2 wt% of the total mass of the electrolyte.
[0079] The first lithium salt is composed of lithium hexafluorophosphate and lithium difluorosulfonylimide in a molar ratio of 1:1; the concentration of the first lithium salt in the electrolyte is 0.8 mol / L.
[0080] Comparative Example 5
[0081] This embodiment provides a low-temperature, high-voltage, high-rate electrolyte, which is composed of fluorosulfonyl solvents, film-forming additives, nitrile solvents, and a first lithium salt.
[0082] The fluorosulfonyl solvent used is dimethylsulfonyl fluoride, and the nitrile solvent used is valerate. The volume percentage of dimethylsulfonyl fluoride and valerate is 30%:70%.
[0083] The film-forming additive is composed of fluoroethylene carbonate and vinylene carbonate in a mass ratio of 1:1, and the amount of film-forming additive added is 5 wt% of the total mass of the electrolyte.
[0084] The first lithium salt is composed of lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalateborate in a molar ratio of 8:2, and the concentration of the first lithium salt in the electrolyte is 1 mol / L.
[0085] Comparative Example 6
[0086] The only difference between this comparative example and Example 4 is that an equal volume of isobutyronitrile is used instead of methyl fluorosulfonyl difluoroacetate; all other steps and conditions are the same as in Example 4.
[0087] Comparative Example 7
[0088] The only difference between this comparative example and Example 4 is that the mass ratio of fluoroethylene carbonate and lithium difluorophosphate is changed to 4:1; all other steps and conditions are the same as in Example 4.
[0089] Comparative Example 8
[0090] The only difference between this comparative example and Example 4 is that no film-forming additive is added; all other steps and conditions are the same as in Example 4.
[0091] The battery performance of the electrolytes of Examples 1-4 and Comparative Examples 1-8 of the present invention when applied to batteries is shown in Table 1.
[0092] Table 1. Battery performance of Examples 1-4 and Comparative Examples 1-8 at different temperatures.
[0093]
[0094] Note: The values of Comparative Example 8 after 100 cycles at -40℃ in Table 1 are not listed; their cycle trend can be found in [the table below]. Figure 1 .
[0095] As shown in Table 1, the initial discharge specific capacity of Examples 1 to 4 at -40℃ was 152.76 to 155.99 mAh / g, and it remained at 149.59 to 153.83 mAh / g after 100 cycles. Among them, Example 4 had the highest initial discharge specific capacity at low temperature and the highest discharge specific capacity after 100 cycles, indicating that it has good low temperature cycling stability.
[0096] Compared to Example 4, Comparative Example 1 exhibited a discharge specific capacity of only 8.45 mAh / g after 100 cycles at -40°C; Comparative Examples 2-6 and 7, under the same conditions, had discharge specific capacities ranging from 84.92 to 135.897 mAh / g, all lower than Example 4. This indicates that when the formulation combination of the present invention is not used or the proportions of key components are changed, the low-temperature cycling performance significantly decreases, demonstrating the synergistic effect of fluorosulfonyl solvents, nitrile solvents, film-forming additives, and the first lithium salt.
[0097] Figure 1Further, it is shown that Examples 3 and 4 maintain relatively stable discharge specific capacity during cycling at -40°C; Comparative Example 1 shows the most significant capacity decay, and the cycling performance of Comparative Examples 6 and 9 is also lower than that of Example 4, which is consistent with the low-temperature cycling results in Table 1.
[0098] Figure 2 The results show that in Example 4, the discharge specific capacity gradually decreased with increasing rate at low temperature, but still remained at 117.48 mAh / g at 5C, indicating that the electrolyte can support high-rate discharge at low temperature.
[0099] The above description is only a part of the embodiments of the present invention and does not limit the scope of protection of the present invention. Any equivalent device or equivalent process transformation made based on the content of the present invention specification and drawings, or direct or indirect application in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A low-temperature, high-voltage, high-rate lithium battery electrolyte, characterized in that: Includes solvents, film-forming additives, and the first lithium salt; The solvent is composed of nitrile solvent and fluorosulfonyl solvent in a volume percentage of (40~70):(60~30); The film-forming additive comprises an ester solvent and a second lithium salt in a mass ratio of (5~10):1; the amount of the film-forming additive is 2~10 wt% of the total mass of the electrolyte. The ester solvent includes at least one of carbonate solvents, sulfate solvents, and sulfite solvents, and the second lithium salt includes at least one of lithium difluorophosphate, lithium dioxaborate, and lithium difluoroborate.
2. The low-temperature, high-voltage, high-rate lithium battery electrolyte according to claim 1, characterized in that: The nitrile solvent is at least one of C2-C5 alkyl nitrile and fluorinated C2-C5 alkyl nitrile.
3. A low-temperature, high-voltage, high-rate lithium battery electrolyte according to claim 1 or 2, characterized in that: The fluorosulfonyl solvent is at least one selected from methyl fluorosulfonyl difluoroacetate, N-pyrrolidinyl sulfonyl fluoride, N,N-dimethylsulfonyl fluoride, N,N-diethylsulfonyl fluoride, ethylsulfonyl fluoride, dimethylsulfonyl fluoride, and 1-butanesulfonyl fluoride; The carbonate solvent includes at least one of ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, and vinylene sulfate; the sulfate solvent includes at least one of vinylene sulfate and propylene sulfate; and the sulfite solvent includes vinylene sulfite.
4. The low-temperature, high-voltage, high-rate lithium battery electrolyte according to claim 3, characterized in that: The solvent is composed of isobutyronitrile and methyl fluorosulfonyl difluoroacetate; and / or; The film-forming additives include fluoroethylene carbonate and lithium difluorophosphate.
5. The low-temperature, high-voltage, high-rate lithium battery electrolyte according to claim 1, characterized in that: The volume percentage of nitrile solvent and fluorosulfonyl solvent in the solvent is (45~50):(55~50).
6. A low-temperature, high-voltage, high-rate electrolyte according to claim 1, 4, or 5, characterized in that: The amount of the film-forming additive is 8-10 wt% of the total mass of the electrolyte.
7. The low-temperature, high-voltage, high-rate lithium battery electrolyte according to claim 6, characterized in that: The first lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bisfluorosulfonylimide, lithium trifluoromethanesulfonate, and lithium bistrifluoromethanesulfonylimide; The concentration of the first lithium salt in the electrolyte is 0.3~2 mol / L.
8. The low-temperature, high-voltage, high-rate lithium battery electrolyte according to claim 1, characterized in that: The electrolyte has an applicable voltage range of 2.8~4.5V, a temperature range of -40~25℃, and a rate range of 0.1~5℃.
9. An application of the electrolyte as described in any one of claims 1 to 8, characterized in that: Used in lithium batteries.
Citation Information
Patent Citations
Carbonic ester electrolyte, preparation method thereof and lithium metal battery
CN117133977A